Comprehensive Analysis of Customer Brand Engagement and Customer-Based Brand Equity in Indonesia’s E-Commerce: Moving Beyond the Holistic View - Carmel Novella Henni; Popy Rufaidah (Dinasti Publisher, 2025)
Due to the intense competition among brands in engaging their customers, this study aims to give a deeper understanding to e-commerce players/ marketer about each customer brand engagement multidimension (conscious attention, enthused participation, and social connection) influences towards customer-based brand equity multidimensions (brand awareness, brand association, perceived quality, and brand loyalty). This study collected data from 297 Indonesian Shopee users using online surveys and evaluated it by Partial Least Squares-Structural Equation Modelling. This study finds that each customer brand engagement dimension has a considerable impact on each customer-based brand equity dimension; particularly, conscious attention has the strongest influence on brand awareness, enthused participation and social connection on brand loyalty. Notably, no previous study has specifically examined the influence of each dimension in Indonesia’s e-commerce industry; most studies have only taken a holistic approach by analysing the overall influence of the variable. This study finding will give a thorough perception to the e-commerce players, which will contribute to their strategy-making consideration in enhancing company’s customer-based brand equity. It also contributed to the theoretical field by providing clarity about each dimension of customer brand engagement influences which will expand the depth of current research findings.